Shakespeare, Antony and Cleopatra, and the nature of fame - Logan, Robert A. (Medieval Institute Publications, Western Michigan University, 2018)
Introduction: Shakespeare's kinetic characterizations – Antony and Cleopatra in seventeenth-century contexts – Immortal longings: Shakespeare's perspective on fame – Standards of measure in Antony and Cleopatra – The varying shore: changing perceptions, sustaining illustriousness – A pair so famous: achieving permanent renown – Shakespeare's imperishable fame
9781580443197
Keywords: Shakespeare; William; Shakespeare; William 1564-1616; Antony and Cleopatra; Fame in literature